2016
DOI: 10.5114/fmpcr/63060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular physical activity on pain, anxiety, and depression in patients with treatment-resistant arterial hypertension

Abstract: Background. Medical experts and professional societies commonly recommend regular physical activity to patients with arterial hypertension. However there is little evidence of the influence of physical exercise on treatment-resistant arterial hypertension. Objectives. the aim of the study was to analyze the influence of physical activity, intensified with additional training support, and followed up with SMS reminders regarding pain, anxiety, and depression in patients with resistant hypertension. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…One study was excluded because the same patients had also participated in previous published research ( 33 ). In addition, another study was excluded because analyses were solely focused on the BP effects of exercise training cessation ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded because the same patients had also participated in previous published research ( 33 ). In addition, another study was excluded because analyses were solely focused on the BP effects of exercise training cessation ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our study confirmed that the proportion of stress among hypertensive patients who were not physically active was higher than those who were active. The systematic physical activity performed by patients with treatment-resistant arterial hypertension reduces anxiety, symptoms of depression and pain intensity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Undertaking physical activity by people of working age is a significant problem. their engagement in physical exercises of appropriate frequency, duration and intensity can not only contribute to the prevention of diseases and maintaining good psychophysical fitness, but it can also ensure full recovery after diseases, injuries or fatigue [5][6][7][8]. as a result, engagement in physical activity allows working-age individuals to successfully fulfill their social, professional, family or sexual functions, and thus it greatly affects their perceived quality of life [9][10][11].…”
Section: Introductionmentioning
confidence: 99%